Implementasi Manajemen Pelayanan KB Dalam Peningkatan Partisipasi Akseptor KB di Puskesmas Paya Lombang Kecamatan Tebing Tinggi Kabupaten Serdang Bedagai - Wibowo, Nazlia; Daulay, Desi Nurhayati; Daulay, Fanny Sasbuhky (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
The success of the KB program is greatly influenced by the effectiveness of service management at the level of basic health facilities such as Community Health Centers. Serdang Bedagai consists of 20 Community Health Centers spread across 17 Districts. Based on data from the Family Information System (SIGA) of the BKKBN Serdang Bedagai, Tebing Tinggi is one of the areas with a fairly high number of active KB acceptors. This study aims to determine the implementation of KB service management in increasing the participation of KB acceptors in the Puskesmas. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the planning of KB services at the Paya Lombang Community Health Center, Tebing Tinggi District, Serdang Bedagai is carried out based on data from fertile couples, implementation is carried out in an integrated manner through fixed and mobile services, and evaluations are carried out periodically. The implementation of good management has been proven to be able to increase the number of active acceptors and new acceptors. It is concluded that the implementation of effective KB service management contributes positively to increasing community participation in the KB program. It is recommended that Community Health Centers continue to improve the capacity of their staff, expand outreach, and ensure the availability of contraceptives.